Managing Major Postpartum Haemorrhage following Acute Uterine Inversion with Rusch Balloon Catheter - Remon Keriakos; Smriti Ray Chaudhuri (Case Reports in Critical Care)
Acute postpartum uterine inversion is a relatively rare complication. The uterus inverts and the uterine fundus prolapses to or through the dilated cervix. It is associated with major postpartum haemorrhage with or without shock. Shock is sometimes out of proportion to the haemorrhage. Minimal maternal morbidity and mortality can be achieved when uterine inversion is promptly and aggressively managed. We present this report of three cases of acute uterine inversion complicated with major postpartum haemorrhage and managed with Rusch balloon. The paper highlights the importance of early recognition and the safety of the use of intrauterine balloon to manage major postpartum haemorrhage in these cases.